Detection of cerebral NAD+ in humans at 7T - Graaf, Robin A.; Feyter, Henk M.; Brown, Peter B.; Nixon, Terence W.; Rothman, Douglas L.; Behar, Kevin L. (Magnetic resonance in medicine, 2017)
Purpose To develop 1H‐based MR detection of nicotinamide adenine dinucleotide (NAD+) in the human brain at 7T and validate the 1H results with NAD+ detection based on 31P‐MRS. Methods 1H‐MR detection of NAD+ was achieved with a one‐dimensional double‐spin‐echo method on a slice parallel to the surface coil transceiver. Perturbation of the water resonance was avoided through the use of frequency‐selective excitation. 31P‐MR detection of NAD+ was performed with an unlocalized pulse‐acquire sequence. Results Both 1H‐ and 31P‐MRS allowed the detection of NAD+ signals on every subject in 16 min. Spectral fitting provided an NAD+ concentration of 107 ± 28 μM for 1H‐MRS and 367 ± 78 μM and 312 ± 65 μM for 31P‐MRS when uridine diphosphate glucose (UDPG) was excluded and included, respectively, as an overlapping signal. Conclusions NAD+ detection by 1H‐MRS is a simple method that comes at the price of reduced NMR visibility. NAD+ detection by 31P‐MRS has near‐complete NMR visibility, but it is complicated by spectral overlap with NADH and UDPG. Overall, the 1H‐ and 31P‐MR methods both provide exciting opportunities to study NAD+ metabolism on human brain in vivo. © 2016 International Society for Magnetic Resonance in Medicine. Magn Reson Med 78:828–835, 2017. © 2016 International Society for Magnetic Resonance in Medicine.